Glucorio – diabetes management system - Roslan, Muhammad Lukman; Nosruddin, Nur Afiqah Rahma; Mansor, Hafizah (IIUM Press, 2020)
Diabetes mellitus is a disease known as the “silent killer” disease that can lead to other chronic diseases. To prevent chronic diseases in diabetic patients, diabetes self-management plays an important role. Our mobile application, ‘Glucorio’ is designed as a tool to help patients in self-management of diabetes. Glucorio is a mobile phone-based diabetes logbook that can be connected to Accu-Chek Guide glucometer through wireless data transfer (Bluetooth) that automates the process of transferring and recording of data. Additionally, the users can also enter the data manually; data such as physical activity, food intake, eating habit tracking and many more. All the records are displayed in the form of charts and graphs to help both patients and doctors in understanding the data clearly through visualisation. The patients can therefore monitor their glucose levels, and this helps them to control their sugar intake. Thus, the patients can improve their health quality and avoid critical conditions in the future.